Enhanced engraftment and repairing ability of human adipose‐derived stem cells, conveyed by pharmacologically active microcarriers continuously releasing HGF and IGF‐1, in healing myocardial infarction in rats. Issue 9 (11th March 2015) - Savi, Monia; Bocchi, Leonardo; Fiumana, Emanuela; Karam, Jean‐Pierre; Frati, Caterina; Bonafé, Francesca; Cavalli, Stefano; Morselli, Paolo G.; Guarnieri, Carlo; Caldarera, Claudio M.; Muscari, Claudio; Montero‐Menei, Claudia N.; et al.
Abstract One of the main cause of ineffective cell therapy in repairing the damaged heart is the poor yield of grafted cells. To overcome this drawback, rats with 4‐week‐old myocardial infarction (MI) were injected in the border zone with human adipose‐derived stem cells (ADSCs) conveyed by poly(lactic‐co‐glycolic acid) microcarriers (PAMs) releasing hepatocyte growth factor (HGF) and insulin‐like growth factor‐1 (IGF‐1) (GFsPAMs). According to treatments, animals were subdivided into different groups: MI_ADSC, MI_ADSC/PAM, MI_GFsPAM, MI_ADSC/GFsPAM, and untreated MI_V. Two weeks after injection, a 31% increase in ADSC engraftment was observed in MI_ADSC/PAM compared with MI_ADSC (p < 0.05). A further ADSC retention was obtained in MI_ADSC/GFsPAM with respect to MI_ADSC (106%, p < 0.05) and MI_ADSC/PAM (57%, p < 0.05). A 130% higher density of blood vessels of medium size was present in MI_ADSC/GFsPAM compared with MI_ADSC (p < 0.01). MI_ADSC/GFsPAM also improved, albeit slightly, left ventricular remodeling and hemodynamics with respect to the other groups. Notably, ADSCs and/or PAMs, with or without HGF/IGF‐1, trended to induce arrhythmias in electrically driven, Langendorff‐perfused, hearts of all groups. Thus, PAMs releasing HGF/IGF‐1 markedly increase ADSC engraftment 2 weeks after injection and stimulate healing in chronically infarcted myocardium, but attention should be paid to potentially negative electrophysiological consequences. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3012–3025, 2015.